2005
DOI: 10.1385/ir:31:3:189
|View full text |Cite
|
Sign up to set email alerts
|

Immunologic Roles of Hyaluronan

Abstract: Hyaluronan (HA), a large glycosaminoglycan composed of D-N-acetylglucosamine and D-glucuronic acid, is expressed in virtually all tissues and has long been considered to serve as a structural component or filling material in the tissue interstitium (Filler Theory). This idea was revised with the discovery of HA-binding proteins that introduced the concept that HA may also serve as an adhesive substrate for cellular trafficking (Adhesion Theory). Most recently, it has been shown that HA fragments can deliver ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
86
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(88 citation statements)
references
References 100 publications
1
86
0
1
Order By: Relevance
“…The views about its function are rapidly expanding because of the latest explorations. Its functions were summarized as filler theory, adhesion theory, and signaling theory, in which, far from an inert structural biopolymer, HA represents a multifunctional carbohydrate mediator of immune processes (24). Our findings propose that HA could be involved in the pathophysiological process of the endothelial cell damage not only in IL-2-induced VLS but in other endothelial damage-related diseases.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…The views about its function are rapidly expanding because of the latest explorations. Its functions were summarized as filler theory, adhesion theory, and signaling theory, in which, far from an inert structural biopolymer, HA represents a multifunctional carbohydrate mediator of immune processes (24). Our findings propose that HA could be involved in the pathophysiological process of the endothelial cell damage not only in IL-2-induced VLS but in other endothelial damage-related diseases.…”
Section: Discussionmentioning
confidence: 77%
“…Pep-1 is a newly isolated peptide that specifically binds to soluble, cell-associated, and immobilized forms of HA. It has been confirmed that Pep-1 inhibits HA function by blocking its molecular interaction with HA-binding proteins (22,24). Figure 1 shows a representative experiment that displayed VLS induced following IL-2 administration in the lungs and liver when compared with the PBS-treated group.…”
Section: Pep-1 Inhibits Vls In C57bl/6 Micementioning
confidence: 79%
See 1 more Smart Citation
“…For example, DCs express CD44, a major HA binding receptor (40), and this could influence trafficking. However, we showed the ability to rescue the loss of DCs by crossing HYAL1-expressing mice into Tlr4 -/-mice, but this was not seen when crossed into Cd44 -/-mice.…”
Section: Discussionmentioning
confidence: 99%
“…HA is synthesized by the HA synthase (HAS) enzymes that are encoded by the corresponding multigene family HAS1, -2, -3a, and -3b (7-10), and its importance in the extracellular matrix is underlined by the expanding range of pathological contexts in which modified or aberrant HA metabolism appears to play a role. These include malignancy, osteoarthritis, and pulmonary and vascular disorders, along with other immune and inflammatory diseases (11)(12)(13)(14)(15)(16)(17)(18)(19). HA has also been implicated in regenerative processes such as wound healing (e.g.…”
mentioning
confidence: 99%